A new class of radiopeptides for PET imaging of neuromedin-B receptor: 68Ga-ranatensin analogs12. Issue 6 (17th May 2016) - Morgat, C.; Varshney, R.; Vimont, D.; Savona-Baron, C.; Riès, C.; Chanseau, C.; Bertrand, S. S.; Mishra, A. K.; Hindié, E.; Fernandez, P.; Schulz, J.
Abstract : The neuromedin B receptor NMB-R is frequently over-expressed in tumors of the lung, pancreas, colon, carcinoids (bronchial, intestinal) and also pruritus. We have developed a new class of radiopeptide for NMB-R targeting. Abstract : The neuromedin B receptor (NMB-R) is a promising target in several human processes, for instance thymic carcinoma, intestinal carcinoids, pruritus, etc. NMB-R Positron Emission Tomography (PET) molecular imaging may be of great value. We here report on the development of the first 68 Ga-ranatensin analog. The ranatensin derivative (Aib-Gln-Trp-Ala-Val-Gly-His-Phe-Met-CONH2, RV_15) was synthesized and conjugated to the DOTA macrocycle with good yield. This chelator is particularly suitable for 68 Ga ( T 1/2 = 67.71 min, β + branching = 89.14%) radiolabeling. Radiochemical purity, hydrophilicity, stability, pharmacological properties, inhibitory concentrations (IC50 ) and biodistribution in normal strain-A mice were investigated. Radiochemical purity of the 68 Ga-ranatensin analog was always >97%. The non-radioactive analog, nat Ga-DOTA–RV_15, was found to be hydrophilic and behaves like an agonist to NMB-R and GRP-R (gastrin-releasing-peptide receptor which is another subtype of bombesin receptor) (EC50 values of 5.6 ± 0.1 × 10 −9 M and 2.1 ± 0.1 × 10 −9 M, respectively). Moreover, it showed nanomolar binding inhibitory concentrations for human NMB-R (IC50 = 3.0 ± 1.1 × 10 −8 M) and somewhat less for human GRP-R (IC50 = 3.2 ± 1.2 × 10 −7 M) in a competitive binding assay. 68 Ga-DOTA–RV_15 is stable in plasma up to 45 minutes. Finally, this 68 Ga-ranatensin agonist demonstrated rapid blood and urinary clearances and uptake in the pancreas and kidneys in normal mice. In conclusion, we have developed a novel class of radiopeptide analogue which potentially could be used for NMB-R molecular imaging.